METODE IQRA’: KAJIAN INOVASI PEMBELAJARAN AL-QUR’AN - M. Jamil Yusuf (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2017)
The obligation of teaching and educating teenagers to be able to read al-Qur`an well and correctly, it actually encompasses the obligation to find out the correct and effective teaching method. The discovery of iqra` method is a real work of AsÃ¢â‚¬â„¢ad Humam seen as an effective innovative learning method and sifnificant strive to reduce the number of the blind of reading-writing al-Quran among childern aged 4-6 years and teenagers generally. The use of the rooted Qaidah Baghdadiyah method amidst moslems seen less effective, student`s motivation was low, and the aplication did not develope instutionally. In the same time, anxiousness among Muslims toward blind of reading and writing al-Quran is increasing and unsettling. The discovery of an innovative al-Qur`an learning method could answer the problem of blind of reading-writing al-Quran in real. The innovasion of iqra` method from process aspect is student center learning process, coaching teacher`s profesionalism, and fun and practical learning approach. From the institional development aspect, TPA/TPQ is approved as instituition that organize non-formal Islamic education for learning of reading al-Quran from an early age. Besides, the existence of TPA/TPQ become stronger with the issued Goverment`s Act number 55 year 2007 about Religious Education, the content of the act stated that educaton of al-quran that consits of TKA/TKQ, TPA/TPQ, Ta`limul Quran lil Aulda (TQA), and any other of the same form. This shows that the strive to eradicate Ã¢â‚¬Âthe blind of reading-writing al-QuranÃ¢â‚¬Â in Indonesia has had a strong base legalization. While the support factors to speed up the innovasion are the informed clarity ideas, have regional support and have good institutional managerial skills.